The changes in the thickness of 1000 - 500 MB and it effects the climate of Iraq - بشرى احمد جواد (College of Education for Women, 2019)
This research paper is about synoptic climate specifically with in the upper air layers using upper air layers maps analysis which are maps of thickness for the level 1000 - 500 MB, that their high average ranges between 100 - 5600 M above surface. This research paper focuses on studying special and temporal variations of the atmosphere thickness above Iraqaccording to this study, it is concluded that atmosphere thickness above Iraq increases towards south with an average of 100 M as compared with north of Iraq. Regarding the temporal variations, it is concluded that atmosphere thickness during hot months. In July, for example, the atmosphere thickness becomes thicker than in January with an average of (250)M in Iraq. It is also found at atmosphere thickness above Iraq increases in recent years, especially in Baghdad. When the atmosphere thickness reaches (5400)M, It is an indication of air front formation on the surface. So, a follow up procedure of these locations above Iraq, which is represented by a line on the weather maps, was used. It appears that the line direction moves away from Iraq and goes toward Turkey in recent years, which means that air north, too. By analyzing the weather maps of pressure air systems (1000)MB accompanied with line thickness, it appears that air depressions mostly accompanies with line thickness (5400)M . Whereas, within the pressure level maps (500)MB, It appears the upper trough of the air depression the most frequent pressure system with thickness line of (5400)M.